1989
DOI: 10.1007/bf00042631
|View full text |Cite
|
Sign up to set email alerts
|

Classification of a world collection of white clover cultivars

Abstract: Morphology, flowering, cyanogenesis and leaf markings of 109 white clover (Trifolium repens L .) cultivars, grown as spaced plants and in small plots, were measured . Principal component analysis and cluster analysis were used to compare cultivars . Cultivars were classified into four broad groups . The most important criteria for distinguishing between groups were leaf size, cyanogenesis and combinations of these . Group I, termed small, included small-leaved, prostrate cultivars ; Group II, termed intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
102
0
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(111 citation statements)
references
References 14 publications
4
102
0
2
Order By: Relevance
“…Low HCN concentration (Crush & Caradus 1995;Lehmann et al 1995) with only 10% of plants cyanogenic (Caradus et al 1989a). Stolon density less than 50% that of HUIA (Caradus et al 1991a).…”
Section: California Ladinomentioning
confidence: 99%
See 2 more Smart Citations
“…Low HCN concentration (Crush & Caradus 1995;Lehmann et al 1995) with only 10% of plants cyanogenic (Caradus et al 1989a). Stolon density less than 50% that of HUIA (Caradus et al 1991a).…”
Section: California Ladinomentioning
confidence: 99%
“…High HCN production with 70% of plants cyanogenic (Caradus et al 1989a). No short/long day induction required for flowering; had consistently high production and concentration of nectar (Norris 1987).…”
Section: Origin and Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning herbage legumes, many studies have been undertaken both at the interspecific level (Prosperi et al, 1989) on annual medics and at the intraspecific level (Caradus et al, 1989) on white clover. Finally, in herbage grasses, most work relating to the relationships between ecological and agronomic traits has been aimed at perennial ryegrass in Europe (studies undertaken by the Welsh Plant Breeding Station: Breese, 1966, 1968;Lorenzetti et al, 1971;Tyler andChorlton, 1976, 1978;Tyler et al, 1984;Humphreys and Eagles, 1988) and also in New Zealand (Forde and Suckling, 1980).…”
mentioning
confidence: 99%
“…In white clover, Bortolini et al (2006) reported that leaf area, plant height, flowering intensity and dry matter production contributed more to discriminate accessions. Flores et al (2004) considered phenology, plant height and diameter and Caradus et al (1989) indicated leaf area and cyanogenesis as the most important aspects to differentiate groups.…”
Section: Sci Agricmentioning
confidence: 99%